Performance of the subcutaneous implantable cardioverter-defibrillator in patients with a primary prevention indication with and without a reduced ejection fraction versus patients with a secondary prevention indication - Boersma, Lucas V; Barr, Craig S; Burke, Martin C; Leon, Angel R; Theuns, Dominic A; Herre, John M; Weiss, Raul; Kremers, Mark S; Neuzil, Petr; Husby, Michael P; Carter, Nathan; Stivland, Timothy M; et al. (Heart rhythm, 2017)
BACKGROUND: The subcutaneous implantable defibrillator (S-ICD) provides an alternative to the transvenous ICD for the prevention of sudden cardiac death, but has not been well studied in the most commonly treated transvenous ICD patient population, namely, primary prevention (PP) patients with left ventricular dysfunction. OBJECTIVE: The analyses in the present study were designed to compare clinical outcomes for PP patients with and without a reduced ejection fraction (EF) and secondary prevention (SP) patients implanted with the S-ICD. METHODS: All patients 18 years and older from the S-ICD IDE study and the EFFORTLESS Registry with available data as of November 18, 2013, were included (n = 856; mean follow-up duration 644 days). Outcomes were evaluated in 2 analyses: (1) comparing all PP patients (n = 603, 70.4%) with all SP patients (n = 253, 29.6%) and (2) comparing all PP patients with an EF ≤35% (n = 379) with those with an EF >35% (n = 149, 17.4%). RESULTS: No differences were observed in mortality, complications, inappropriate therapy, or ability to convert ventricular tachyarrhythmias between SP and PP patients. However, SP patients had a higher incidence of appropriate therapy than did PP patients (11.9% vs 5.0%; P = .0004). In the PP subanalysis, the cohort with an EF ≤35% had significantly older patients with more comorbidities and higher mortality (3.0% annually vs 0.0%). Despite these differences, device-related complications, conversion efficacy, and incidence of inappropriate shock therapies were not significantly different between PP subgroups. CONCLUSION: The S-ICD performs well in protecting patients with either PP or SP implant indications from sudden cardiac death. Within PP patients, device performance was independent of EF.
Keywords: senioři; Tachycardia, Ventricular; Outcome and Process Assessment, Health Care; Stroke Volume; Ventricular Dysfunction, Left; dysfunkce levé srdeční komory; protetické vybavení; Defibrillators, Implantable; Subcutaneous ICD; lidé; náhlá srdeční smrt; výsledky a postupy - zhodnocení (zdravotní péče); elektrická defibrilace; Kaplan-Meier Estimate; Middle Aged; registrace; mužské pohlaví; Kaplanův-Meierův odhad; Adult; Electric Countershock; Secondary prevention; Secondary Prevention; Registries; tepový objem; ženské pohlaví; Humans; Death, Sudden, Cardiac; defibrilátory implantabilní; lidé středního věku; Primary Prevention; Appropriate shock; Prosthesis Fitting; dospělí; Ejection fraction; Female; Aged; primární prevence; Primary prevention; komorová tachykardie; sekundární prevence; Male